China’s Trade Relations with Chile : Mutual Benefit or Unequal Dependence? - Osadchaia, Inessa (2025)
This thesis investigates the trade relationship between Chile and China. The purpose is to determine whether these trade relations promote mutual benefit or lead to Chile's dependence on China. This is done by identifying areas of trade imbalance and assessing potential risks to the Chilean economy. This study, based on the analysis of trade data, direct investment flows from China to Chile, historical context and secondary sources, including scholarly articles, covering the past two decades with particular focus on recent trends. The results indicate that if Chile continues to rely heavily on China for trade without diversifying its export basket and partners, this could lead to dependence on China's policies and economic growth.